PENGARUH KONDISI KEUANGAN, OPINI AUDIT SEBELUMNYA, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROBABILITAS PENERIMAAN OPINI AUDIT GOING CONCERN - Nanik Niandari (Akademi Akuntansi YKPN Yogyakarta, 2016)
This study aimed to prove the effect of financial conditions, prior audit opinion, and company growth on acceptance of going concern opinion. This research used manufacturing company listed in Indonesian Stock Exchange (BEI) which taken by purposive sampling method. During three years observations (2011-2013), there were 304 observations and only 28 companies (9.21%) of the observed company got going concern opinion. Using logistic regression analysis, it was found that only financial conditions and prior audit opinion variable that affect going concern acceptance variable. Company Growth were not statistically significant. Keywords: Financial Condition, Prior Audit Opinion, Company Growth, and Going Concern Opinions